Troublesome access: Non-admission experiences in the competitive finnish higher education - Ulpukka Isopahkala-Bouret (MDPI AG, 2025)
In this study, I address policy aims to reconcile equality of opportunity and marketization by examining difficulties in access to Finnish higher education. Finnish higher education is largely funded by the state and has no tuition fees. However, new demands have arisen that align with market-driven policy. At the same time, the Finnish system is one of the most competitive systems in the Organization for Cooperation and Development (OECD), and around 70% of applicants do not gain admittance. The purpose of this study is to examine how prospective degree students who have applied without being allowed to start studying toward a degree respond to the loss of opportunity and position themselves in the higher education marketplace. The analysis is based on 50 online narratives. The results are elaborated into three exploratory story models: (1) ‘Never give up on your dreams’; (2) ‘Need to figure out a new plan’; and (3) ‘You can’t get everything you want in life’. The stories show that marketization of higher education affects the experiences and expectations of prospective students. Moreover, marketization offers opportunities differently for those who already have plenty of resources to compete for access to higher education and those who do not.